Activated eosinophil plays a role in promoting fibrosis in endometriotic lesion - Yosuke Ono; Kota Tanaka; Erina Sato; Masami Ito; Di Zhang; Masako Honda; Tatsuyuki Ogawa; Hikaru Tagaya; Tomohiko Fukuda; Youichi Shinozaki; Kazuyoshi Kato; Schuichi Koizumi; et al. (Scientific Reports)
Abstract The fibrosis mechanism in endometriosis is not elucidated. We investigated the role of eosinophil in fibrosis of endometriosis. The endometriotic stromal cells (ESCs) and endometrial epithelial cells (EECs) were subjected to in vitro experiments. Within endometriotic lesions, eosinophils were prominently observed by Hematoxylin-Eosin (HE) staining. Immunohistochemical staining for Major Basic Protein (MBP), a granule protein of eosinophils, revealed that MBP-positive eosinophils were predominantly found in the endometrial stromal region beneath the epithelial cell layer. Eosinophil clusters were found in 17 of 18 ovarian endometrioma (EMoma) cases, compared to 3 of 16 in non-endometriotic ovarian cyst/tumor (non-EMoma) (P < 0.0005). HE staining revealed eosinophils in fibrotic areas, and fields with ≥ 3 eosinophils per 100 × 100 μm area showed higher counts of nucleolus-positive fibroblasts (P < 0.05). Serial Masson Trichrome staining revealed blue-stained extracellular matrix around MBP-positive eosinophils, indicating fibrosis. GM-CSF levels, a stimulator of eosinophils, were higher in EMoma contents (93.6 ± 16.9 pg/ml) compared to non-EMoma (3.6 ± 2.1 pg/ml, P < 0.05). Coculture of eosinophils with ESCs or EECs upregulated PAI-1 mRNA and protein expression. Immunohistochemistry confirmed PAI-1 expression in eosinophil-rich lesions. These findings suggest that eosinophils promote fibrosis in endometriosis through PAI-1 induction, offering new therapeutic targets.